Prevalence of environmental degradation in natural resource management - Philémon Mafany George (African Journal of Environmental Economics and Management, 2018)
The predominance of environmental degradation in Africa has generated waves of concern from international and national non-governmental organizations (NGOs). Since the 1990s there has been a remarkable increase in the number of NGOs with environmental protection interest in the South. The paper appraises the involvement of NGOs and stakeholder community in environmental protection projects in terms of resource mobilization, organizational strengthening and the institutional development of civil society. The paper which is a product of field investigations concludes that these NGOs are having a significant impact on the social, political and economic life of their populations. However there is the question of their sustainability as local NGOs derive most of their inspiration and resources from NGOs in the North. There is need to appreciate the issues surrounding capacity building beyond technical and sectoral aims. Capacity building must contribute to the long-term organizational strengthening and institutional development of civil society as a whole.